Evaluation of Roche Amplicor PCR assay for Mycobacterium tuberculosis. - Wobeser, W L (1996)
The Roche Amplicor Mycobacterium tuberculosis PCR test (RMtb-PCR) was compared with mycobacterial culture, with the BACTEC 460 system and inoculation on Lowenstein-Jensen media. Results were interpreted with an adjusted "gold standard" incorporating clinical diagnosis. A total of 1,480 clinical specimens from 1,155 patients, including tissues and fluids, as well as 141 specimens which demonstrated a positive growth index on the BACTEC 460 system were assessed. The sensitivity, specificity, and positive and negative predictive values of RMtb-PCR compared with the adjusted gold standard for clinical specimens were 79, 99, 93, and 98%, respectively. In smear-positive specimens, the sensitivity of RMtb-PCR was 98% versus 53% for smear-negative specimens. When RMtb-PCR was performed two times per week, PCR results were available an average of 21 days before the culture results. For specimens demonstrating a positive growth index on the BACTEC 460 system, RMtb-PCR had a sensitivity and specificity of 98 and 100%, respectively. This study demonstrates the value of a commercial nucleic acid amplification kit for rapid diagnosis of M. tuberculosis, particularly in smear-positive specimens or BACTEC culture-positive specimens.